Wednesday

April 16, 2014

April 16, 2014

Posted by **Jim** on Sunday, September 27, 2009 at 12:35am.

(-8b^2)=

-8b^2=

- Algebra 1A -
**PsyDAG**, Sunday, September 27, 2009 at 1:54pm(-8b)^2 = -8b * -8b

-8b^2 = (-8b^2) = -8 * b * b

Substitute 10 for b to evaluate.

**Related Questions**

MATH - EVALUATW (-8B)^2 AND -8B^2 WHEN B=10. (-8B^2)= -8B^2= SOLVE USING THE ...

Algebra 1 - Give the reason (property) for each step in the simplification. 8(a...

Math - How would I do: sqrt32a^8b + sqrt50a^16b Are the exponents 8b and 16b or ...

Math - Can someone please help me with an algebra problem? -|4-8b|=12 I really ...

ALGEBRA - Use the definition of logarithm to simplify each expression. (a) )log_...

Algebra - Multiply 5a^3+4a^2 8b^6-6ab^6 _________ * __________ 6ab-8b 5a^2+4a

algebra - Identify the property or rule that justifies each step in the ...

algebra 1 - 7a+[4a-6b-(8a+2b)] ok so you would get this 7a+[4a-6b-8a-2b]<--- ...

Algebra 1 - 2+11b=8b+15

Algebra - Multiply: (4b + 1/2)(8b - 3/4)